Asymmetrical responding to male versus female other‐race categories in 9‐ to 12‐month‐old infants. - Damon, Fabrice; Quinn, Paul C.; Méary, David; Pascalis, Olivier (British Journal of Psychology)
Faces can be categorized along various dimensions including gender or race, an ability developing in infancy. Infant categorization studies have focused on facial attributes in isolation, but the interaction between these attributes remains poorly understood. Experiment 1 examined gender categorization of other‐race faces in 9‐ and 12‐month‐old White infants. Nine‐ and 12‐month‐olds were familiarized with Asian male or female faces, and tested with a novel exemplar from the familiarized category paired with a novel exemplar from a novel category. Both age groups showed novel category preferences for novel Asian female faces after familiarization with Asian male faces, but showed no novel category preference for novel Asian male faces after familiarization with Asian female faces. This categorization asymmetry was not due to a spontaneous preference hindering novel category reaction (Experiment 2), and both age groups displayed difficulty discriminating among male, but not female, other‐race faces (Experiment 3). These results indicate that category formation for male other‐race faces is mediated by categorical perception. Overall, the findings suggest that even by 12 months of age, infants are not fully able to form gender category representations of other‐race faces, responding categorically to male, but not female, other‐race faces.